The Effect of Family Income During Childhood on Later-Life Attainment: Evidence from Germany - Stephen P. Jenkins; Christian Schluter (Institute for the Study of Labor (IZA), 2002)
We examine the impact of family income during childhood on the type of secondary school that German children attend, a good indicator of their lifetime socioeconomic attainment. By contrast with several US child outcome studies, we find that late-childhood income is a more important determinant of outcomes than early-childhood income, and income effects are not greater for poor households compared to rich households, other things equal. The income effects are small for native-born German children and non-existent for children from guestworker households. Income effects are also small relative to the impact of differences in parental educational qualifications or institutional factors related to the federal state of residence.
Keywords: D31; J13; I32; I21; 330; child poverty; educational achievement; schooling; family background; Bildungsniveau; Sozialer Status; Haushaltseinkommen; Familiensoziologie; Schätzung; Deutschland